Taxonomic Enumeration of Common Plants of Changbhakhar Forest Division, Madhya Pradesh - Suri, S. K. (Indian Forester, 1978)
Based on the field studies of flora of Changbhakhar Forest Division (Madhya Pradesh) during stock mapping, taxonomic enumeration of common plants occurring in the Division has been given in this paper.